Desenvolvimento sustentável e empregos verdes como uma perspectiva de novo mercado - Magalhães, Erica Veloso (2017)
In the face of the global environmental crisis through climate change, discussions on sustainability have grown in academia and in society. Making the change from the current production environment to environmentally friendly production means is the most importance in order to avoid the depletion of natural resources and perpetuate our existence on the planet. The present master dissertation presents green jobs as a new market perspective, so that jobs contribute both to reducing the environmental impact of businesses and economic sectors, as well as creating new decent jobs and including more people in the labor market. The general objective of this research is to highlight green jobs as a fundamental element in the promotion of sustainable development, enabling the promotion of decent work, with the specific objectives of emphasizing the use of environmental management by companies in strengthening responsibility for the environment ; Present the green jobs that are essential in the transition to a sustainable economy; Study the green economy as an ally in the achievement of sustainable development and show sustainable development as a fundamental element in the preservation of natural resources. For the development of this work are used the methods of qualitative and bibliographic approach, obtaining the history and the concept of sustainable development and the green economy, environmental management and socio environmental responsibility and the emergence of green jobs with their repercussions in the world of job. Through the research we can see the importance of green jobs in achieving sustainable development by responding to the social aspect of the tripod that underlies this thinking, providing gains for all actors of the economy.